2022
DOI: 10.1007/s00300-022-03031-6
|View full text |Cite
|
Sign up to set email alerts
|

Short note: extracellular export and consumption of glucose in Antarctic sea ice

Abstract: Extracellular carbohydrate production is widespread in sea ice microbial communities, being produced by both algae and bacteria. Under stressful conditions, including nutrient limitation and high light, cells may export excess fixed carbon as glucose. Glucose microsensors were used to measure extracellular glucose exudation and consumption in a sea ice algal community. Glucose export increased with increasing irradiance between 15 and 512 µmol photons m−2 s−1. This export correlated with declining FvFm values … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Indeed, the composition of DOC exudates of sea-ice inhabiting microorganisms is dominated by glucose, which often constitutes more than 70% of the total. 95 Recently, Piontek et al 84 confirmed that sea-ice polysaccharide composition is dominated by glucose (42–87 mol %). In accordance with that, in our study, seawater samples closer to the ice edge and influenced by sea-ice melt (stations above 81°N) contained more dissolved sugars, particularly glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the composition of DOC exudates of sea-ice inhabiting microorganisms is dominated by glucose, which often constitutes more than 70% of the total. 95 Recently, Piontek et al 84 confirmed that sea-ice polysaccharide composition is dominated by glucose (42–87 mol %). In accordance with that, in our study, seawater samples closer to the ice edge and influenced by sea-ice melt (stations above 81°N) contained more dissolved sugars, particularly glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Since the main component of dissolved carbohydrates is glucose, freshly produced DOM in surface waters and sea ice was characterized by glucose proportions of up to 86%. Indeed, the composition of DOC exudates of sea-ice inhabiting microorganisms is dominated by glucose, which often constitutes more than 70% of the total . Recently, Piontek et al confirmed that sea-ice polysaccharide composition is dominated by glucose (42–87 mol %).…”
Section: Resultsmentioning
confidence: 99%